Patterns in Psychiatrists’ Prescription of Valproate for Female Patients of Childbearing Age With Bipolar Disorder in Japan: A Questionnaire Survey - Tachibana, Masumi; Hashimoto, Tasuku; Tanaka, Mami; Watanabe, Hiroyuki; Sato, Yasunori; Takeuchi, Takashi; Terao, Takeshi; Kimura, Shou; Koyama, Akio; Ebisawa, Sachie; Shizu, Yuichiro; Nagase, Teruyoshi; et al. (Frontiers in Psychiatry, 2020)
Background: Accumulating evidence has shown that valproate has the greatest teratogenic potential for increasing the risk of major congenital malformations, such as neural tube defects, cleft palate, and neurodevelopmental disability. Although valproate is a pharmacological option for acute mania and is used as a stabilization drug for patients with bipolar disorder, some global guidelines state that valproate should not be used for girls or women of childbearing age with bipolar disorder. We investigated patterns in psychiatrists’ prescription of valproate for bipolar female patients of childbearing age in Japan. Methods: From March to May 2018, we conducted a questionnaire survey among psychiatrists from all prefectures in Japan on psychiatric practice as it relates to major depression and bipolar disorder throughout women's life. The questionnaire had two parts: (1) assessment of participating psychiatrists’ backgrounds and attitudes toward patients and (2) their patterns of prescription of psychotropics for female patients with mood disorders across generations and periods of pregnancy. Each question item had four response options: “not at all,” “rarely,” “sometimes,” and “frequently.” We examined patterns of prescription for childbearing-aged women (late adolescence/young adulthood aged 18-24 years, childbearing-age, older adults aged 25-49 years) and pregnant women. Results: In total, 571 psychiatrists (427 males, 123 females, and 21 unknowns) responded appropriately to the questionnaire, including 320 who examined at least one or more late adolescence/young adulthood bipolar women. Approximately 70% of psychiatrists answered that they frequently or sometimes prescribed valproate for bipolar women of childbearing age [late adolescence/young adulthood: not at all, n = 23 (7.5%); rarely, n = 69 (22.5%); sometimes, n =116 (37.8%); and frequently, n = 99 (32.2%); childbearing-age, older adults: not at all, n = 13 (2.7%); rarely, n = 67 (13.8%); sometimes, n = 185 (38.1%); and frequently, n = 220 (45.4%)]. The proportion of general hospital psychiatrists who answered “not at all” or “rarely” to the frequency of their valproate prescriptions was higher than that of psychiatrists working in other medical facilities (χ2(3) = 18.2, p < 0.001). Conclusion: Most psychiatrists frequently or sometimes prescribe valproate for women of childbearing age in Japan.